Impact of Process and Product Modularity (PM) on Competitive Performance of Thailand manufacturing firms: Mediating role of Supply Chain Quality Integration (SCQI) - Waleerak Sittisom; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
This study empirically investigates the relation between modularity and the impact it has on competitive performance of firms. It focuses on both the dimensions of modularity including   process and product modularity. With the vast development of SCQI in firms, this research emphasizes the quality management perspective of firms by assimilating supply chain integration system with it. SCQI system has attained a significant attention over the world that allow firms to strategically collaborate its outer and inner SCI procedures in order to obtain great level quality and modest performance. Using survey method, this research method has opted to gain information through the use of questionnaires the manufacturing firms of Thailand. The information gathered from the organizations are in the form of 304 respondents is analyzed by using statistical tools including SPSS and AMOS by running various tests such as descriptive statistics, reliability tests, CFA and SEM analyze the theoretical relationships among various factors and variables. The outcomes of this research transparently show that both process and Signify a positive association with competitive performance of firms. It also signifies the mediation role of SCQI between modularity and functioning. It means that integrated supply chain practices enhance the development of high-quality commodities. It also helps firms in improving their set up processes by reducing costs and delivery timings to the end users that effectively influence competitive strategies.